2003
DOI: 10.1186/1471-2369-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in chronic dialysis patients in the United states: risk factors for hospitalization and mortality

Abstract: BackgroundThe incidence and risk factors for hospitalized atrial fibrillation have not been previously assessed in a national population of dialysis patients.MethodsWe analyzed the United States Renal Data System (USRDS) Dialysis Morbidity and Mortality Study (DMMS) Wave II in a historical cohort study of hospitalized atrial fibrillation. Data from 3374 patients who started dialysis in 1996 with valid follow-up times were available for analysis, censored at the time of renal transplantation and followed until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
102
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 37 publications
9
102
1
6
Order By: Relevance
“…As such, previously-reported findings of associations between various patient factors, at least those identified upon dialysis initiation, and chronic AF can be robustly quantified. As expected, we echoed the finding of the association of age with AF reported by Wizemann et al in the DOPPS database 8 , Abbott et al (in a univariate analysis) in Dialysis Morbidity and Mortality (DMMS) Wave II study 18 , Vasquez et al in their small but well-studied incident dialysis cohort 11 , and others 5,7 . Both Abbott et al and Wizemann et al also found Caucasian race to be associated with AF 8,18 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As such, previously-reported findings of associations between various patient factors, at least those identified upon dialysis initiation, and chronic AF can be robustly quantified. As expected, we echoed the finding of the association of age with AF reported by Wizemann et al in the DOPPS database 8 , Abbott et al (in a univariate analysis) in Dialysis Morbidity and Mortality (DMMS) Wave II study 18 , Vasquez et al in their small but well-studied incident dialysis cohort 11 , and others 5,7 . Both Abbott et al and Wizemann et al also found Caucasian race to be associated with AF 8,18 .…”
Section: Discussionsupporting
confidence: 53%
“…As expected, we echoed the finding of the association of age with AF reported by Wizemann et al in the DOPPS database 8 , Abbott et al (in a univariate analysis) in Dialysis Morbidity and Mortality (DMMS) Wave II study 18 , Vasquez et al in their small but well-studied incident dialysis cohort 11 , and others 5,7 . Both Abbott et al and Wizemann et al also found Caucasian race to be associated with AF 8,18 . The DOPPS investigators also found BMI to be significantly correlated in direct fashion with preexisting AF 8 .…”
Section: Discussionsupporting
confidence: 53%
“…Another study found no difference (P ϭ 0.4) in the incidence of stroke when comparing an "undertreated" population (24% prevalence of warfarin use in patients with atrial fibrillation; n ϭ 127) with patients without atrial fibrillation (n ϭ 349) in the same cohort. 41 Abbott et al 42 reported a survival advantage in 123 hospitalized dialysis patients who had atrial fibrillation and were on warfarin; however, the results apply to a specific subpopulation of patients who survived hospitalization for atrial fibrillation and were presumed to be on warfarin before admission to hospital. 42 Overall, limited hypotheses can be generated from these studies because of methodologic limitations and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Nós mostramos baixa prevalência de FA quando comparado a outros dados publicados em pacientes sob hemodiálise. Acar et al 13 encontraram prevalên-cia de 13,1% em uma análise de 183 pacientes com idade média de 52 anos e tempo médio de TRS de 41,6 meses, características semelhantes às encontradas em nossa amostra populacional; os pacientes com FA tinham idade média de 64,9 ± 9,8 estatisticamente mais elevada que o grupo sem FA que era de 49,9 ± 16,6 (p < 0,001).…”
Section: Discussionunclassified